Preoperative Pain is the Strongest Predictor of Postoperative Pain and Diminished Quality of Life after Ventral Hernia Repair. Issue 8 (August 2013) - Tsirline, Victor B.; Colavita, Paul D.; Belyansky, Igor; Zemlyak, Allay; Lincourt, Amy E.; Heniford, B. Todd
With evolution of hernia repair surgery, quality of life (QOL) became a major outcome measure in nearly 350, 000 ventral hernia repairs (VHRs) performed annually in the United States. This study identified predictors of chronic pain after VHR. A prospective database of patient-reported QOL outcomes at a tertiary referral center was queried from 2007 to 2010; 512 patients met inclusion criteria. Factors including demographics, medical comorbidities, preoperative symptoms, and hernia characteristics were analyzed using advanced statistical modeling. Average age was 56.4 years, 57.6 per cent were males, mean body mass index was 33 kg/m 2, hernia defect size was 138 cm 2, and 35.5 per cent were repaired laparoscopically. Preoperatively, 69 per cent of patients had mild and 28 per cent severe pain during some activities. Pain levels were elevated in the first month postoperatively; by 6 months, patients reported significant improvement. The most significant and consistent predictor of postoperative pain was the presence of preoperative pain (odds ratio, 2.1; 95% confidence interval, 1.4 to 3.0; P = 0.0001). Older patients and men had less postoperative pain, but they also had less preoperative pain, so these factors were not independent predictors. Patients with minimal preoperative symptoms uniformly experienced resolution of pain by 6 months postoperatively. Among patients with severe preoperative pain, one-third reported long-term resolution of pain, and one-third had persistent severe pain. The former group had smaller hernias (91 vs 194 cm 2, respectively, P = 0.015). Cases of new-onset, long-term pain after VHR were rare (less than 2%). Most patients' symptoms resolve by 6 months after surgery, but those with severe preoperative pain are at risk for persistent postoperative pain.